PENERAPAN PERMAINAN ROLET ALFABET UNTUK MENINGKATKAN KEMAMPUAN BAHASA ANAK KELOMPOK B RA AL – FATTAH KARANGDUREN PAKISAJI MALANG - Denok Suhartatik; Ika Ratih Sulistiani; Yorita Febry Lismanda (UNISMA, 2019)
This study analyzes the problems that occur in RA Al-Fattah Karangduren about low language skills. This is due to the frequent use of worksheets and magazines, teachers are less creative in attracting children’s interest and the lack of play elements so that children become passive an quickly get bored. In fact, the essence of learning in kindergarten is playing, therefore the researchers took the initiative to use the alphabet roulette game which is equipped with word cards and picture cards. In this game children are invited to play directly so that children get new experiences and are easy to understand the material presented. In addition, this game makes it easier for children to understand the letter symbol shape, understand the word and interpret every picture that is there. Form the results of the research action it was found that 1) the ability to mention letters had increased from 68.4% (in the first cycle) to 90.8% (in the second cycle). 2) the ability to mention words had increased from 57.9% (in first cycle) to 80.3% (in the second cycle), 3) the ability to pair images with words has increased from 52.6% (in the first cycle) to 88.2% (in the second cycle).